Energy modelling and the Nexus concept. (January 2018) - Brouwer, Floor; Avgerinopoulos, Georgios; Fazekas, Dora; Laspidou, Chrysi; Mercure, Jean-Francois; Pollitt, Hector; Ramos, Eunice Pereira; Howells, Mark
Abstract: The Nexus concept is the interconnection between the resources energy, water, food, land and climate. Such interconnections enable to address trade-offs and seek for synergies among them. Several policy areas (e.g. bio-based economy, circular economy) increasingly consider the Nexus concept. Ignoring synergies and trade-offs between energy and natural flows, can generate misleading modelling outcomes. Several modelling tools are available to address energy and the Nexus. Based on six such models, this paper aims to support the design and testing of coherent strategies for sustainable development. Model improvements would be achieved by comparing model outcomes and including a common baseline. Highlights: The Nexus concept enables to address trade-offs and seek for synergies among energy, water, food, land and climate. Ignoring synergies and trade-offs between energy and other natural flows, can generate misleading modelling outcomes. Modelling tools are available to address energy and the Nexus. Model improvements would be achieved by comparing model outcomes, including a common baseline.